On the shoulders of giants (part one): inspiring residential child care - Keith White (Scottish Journal of Residential Child Care)
This paper will be one of a series of two papers based on the keynote speech given by Keith White at the SIRCC conference on 7th June, 2007. The first paper in this series will begin by identifying a few of the historically significant figures in residential child care. It will then summarise four key messages which have emerged from this examination of history. The life and work of Janusz Korczak, one of the 'giants' on whose shoulders residential staff should seek to stand, will be revisited to demonstrate how principles of care are put into practice. The paper will then go on to discuss briefly five principles of practice which may be used to guide residential child care. The second paper in the series, which will be published in the next issue of the Journal, will focus on the life of Pandita Ramabai, an extraordinary woman who lived an extraordinary life in extraordinary times. Reflections on the life and work of Ramabai in terms of the principles of practice will be discussed with a view to inspiring residential child care staff in their everyday work.